WELDING SHOPS IN AUTOMOBILE PRODUCTION UZ AUTO: REVIEW, TECHNOLOGIES, CHALLENGES AND PROSPECTS - Jurayev Abdullajon Ibragimovich (Modern American Journals, 2025)
This review focuses on welding workshops in Uz Auto vehicle body production, which play a key role in ensuring the strength, safety, and durability of vehicles. The work examines various aspects, from the history and evolution of welding technologies used in automotive manufacturing to modern methods used in modern production processes. Robotic welding systems, their advantages, and challenges related to integration and maintenance are examined in detail. Special attention is paid to the quality of welded joints, quality control methods, and non-destructive testing used to detect defects.
Keywords: Welding, automotive, robotic welding, spot welding, arc welding, laser welding, friction welding with stirring, quality control, non-destructive testing, steel, automation